Implementasi Model Pendidikan Full Day School dalam Membentuk Karakter Religius di SMP Muhammadiyah PK Bayat - Nuryahya, Ikhsan; Subando, Joko (Lembaga Yasin AlSys, 2025)
Education plays a strategic role in shaping the character of the younger generation as a foundation for national progress, particularly through the cultivation of religious character, which is among the 18 core character values outlined by the Ministry of National Education. This study aims to describe the implementation of the Full Day School (FDS) semi-pesantren education model in developing students’ religious character at SMP Muhammadiyah Program Khusus Bayat, Klaten. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. The findings indicate that the Islamic-based FDS model is effective in fostering students’ religious character through the integration of religious programs such as congregational prayer, dzikir, murajaah, and the habituation of other virtuous practices. Challenges include varying levels of student discipline; however, overall, the model successfully promotes the development of academically competent students with noble character and spiritual integrity. These findings suggest that the semi-pesantren FDS model offers a strategic alternative to address the moral crisis among youth and supports the achievement of national education goals.